<DATA REPORT>RIOMETER RECORDS OF 30 MHz COSMIC NOISE AT SYOWA STATION, ANTARCTICA IN 1978 - OSE, Masami; IGARASHI, Kiyoshi; TSUZURAHARA, Shigehiko (National Institute of Polar Research, 1979)
P(論文) departmental bulletin paper